2012
DOI: 10.1089/acm.2011.0488
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Reducing Effects of Real and Artificial Nature in a Hospital Waiting Room

Abstract: Objectives: This field study investigated the potential stress-reducing effects of exposure to real or artificial nature on patients in a hospital waiting room. Additionally, it was investigated whether perceived attractiveness of the room could explain these effects. Design: In this between-patients experimental design, patients were exposed to one of the following: real plants, posters of plants, or no nature (control). These conditions were alternately applied to two waiting rooms. Location: The location of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 30 publications
(31 reference statements)
4
93
0
4
Order By: Relevance
“…Nature exposure therapy has been found to be effective for clinical stress management (Villani & Riva, 2012), and stress and anxiety reduction for deployed military medics (Stetz et al, 2011). Nature posters and plants in hospital waiting rooms have been shown to reduce patient stress (Beukeboom, Langeveld, & Tanja-Dijkstra, 2012) and even perceptions of pain after undergoing painful bone marrow aspiration and biopsy (Lechtzin et al, 2010). From these studies, it is evident that exposure to nature reliably produces improvements in affect and reductions in both perceived and physiological stress, with the minimum requirement for the effects being brief viewing of nature scenes.…”
Section: Restorative Effects Of Naturementioning
confidence: 99%
“…Nature exposure therapy has been found to be effective for clinical stress management (Villani & Riva, 2012), and stress and anxiety reduction for deployed military medics (Stetz et al, 2011). Nature posters and plants in hospital waiting rooms have been shown to reduce patient stress (Beukeboom, Langeveld, & Tanja-Dijkstra, 2012) and even perceptions of pain after undergoing painful bone marrow aspiration and biopsy (Lechtzin et al, 2010). From these studies, it is evident that exposure to nature reliably produces improvements in affect and reductions in both perceived and physiological stress, with the minimum requirement for the effects being brief viewing of nature scenes.…”
Section: Restorative Effects Of Naturementioning
confidence: 99%
“…The latter may operate by way of the mechanism of biophilia, the theory that there is an instinctive bond between human beings and other living systems (Wilson, 1984;see, e.g. Beil and Hanes, 2013;Beukeboom et al, 2012;Lottrup et al, 2013;van den Berg et al, 2010;Ward Thompson et al, 2012), or through reduction in noise annoyance (e.g. trees and greenery absorb sound from traffic) (Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The ceiling artwork contributed positively to patients' experience during radiation therapy treatment [28]. Beukeboom et al [29] has found that the more aesthetic the patient room is, the lower is the stress level of persons participating in medical procedures there. Much attention is also paid to hiding the medical infrastructure.…”
Section: The Redefinition Of Medical Space Through Visual Artmentioning
confidence: 99%